Morphology of the Liver of Asian Elephant (Eelephas maximus indicus) - Rajani, C.V. (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on liver collected from an elephant calf and 5 adult domesticated Asian elephants. After recording gross morphological features, liver samples were processed for routine histological procedures. Liver had four borders viz., dorsal, ventral, left lateral and right lateral. Caudal vena cava crossed the dorsal border and the ventral border had a deep umbilical fissure. Parietal surface presented straight line of attachment of Falciform ligament and an inverted arc-like coronary ligament. Visceral surface had a wide hepatic porta and attachment of lesser omentum. Liver had two chief lobes: a larger right lobe and an undivided left lobe. The round ligament was attached to the right medial lobe. Liver did not adhere to right kidney. Gall bladder was absent. Liver showed dense Glisson’s capsule. The hepatic lobules were indistinctly delineated and irregularly hexagonal. Radiating, branching laminae of hepatocytes and intervening anastomosing sinusoids constituted the parenchyma. Small squamous endothelial cells and large Kupffer cells lined the sinusoids. Portal triads were observed at the periphery of the lobule. The present study established the morphological and histological characteristics of liver in Asian elephant.